2016
DOI: 10.1016/j.cct.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Identifying effective and feasible interventions to accelerate functional recovery from hospitalization in older adults: A randomized controlled pilot trial

Abstract: Hospitalization induces functional decline in older adults. Many geriatric patients fail to fully recover physical function after hospitalization, which increases the risk of frailty, disability, dependence, re-hospitalization, and mortality. There is a lack of evidence-based therapies that can be implemented following hospitalization to accelerate functional improvements. The aims of this Phase I clinical trial are to determine 1) the effect size and variability of targeted interventions in accelerating funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 80 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…In frail but otherwise-healthy older adults, an adequate (15 g) supplementation of high-quality protein at breakfast and lunch was shown to increase physical function. In addition, we recently reported that 30 days of protein supplementation (20 g twice daily) was feasible and increased physical function as measured by the short physical performance battery in older patients after an acute hospitalization [ 51 , 52 ]. The benefits of protein/amino acid supplementation on skeletal muscle health has been shown to be achievable during a 2–3 week time frame in clinical populations [ 53 ] or models of clinical settings [ 54 ].…”
Section: Critical Illness and Recoverymentioning
confidence: 99%
“…In frail but otherwise-healthy older adults, an adequate (15 g) supplementation of high-quality protein at breakfast and lunch was shown to increase physical function. In addition, we recently reported that 30 days of protein supplementation (20 g twice daily) was feasible and increased physical function as measured by the short physical performance battery in older patients after an acute hospitalization [ 51 , 52 ]. The benefits of protein/amino acid supplementation on skeletal muscle health has been shown to be achievable during a 2–3 week time frame in clinical populations [ 53 ] or models of clinical settings [ 54 ].…”
Section: Critical Illness and Recoverymentioning
confidence: 99%
“…CR programs can help transition patients with HF from hospitalization-to-home as well as from skilled nursing facility-to-home with valuable supervision and guidance of physical activity to reduce the effects of hospital-related deconditioning. 19 CR programs also provide opportunities to review medications and goals of care to ensure management is well-directed, wellcoordinated, and patient-centered. This reduces the chance of unchecked medication interactions and unnecessary polypharmacy.…”
Section: Hf In Older Adults: Competing Challenges Of Managementmentioning
confidence: 99%
“…Within the framework of the Third National Health and Nutrition Examination Survey, Srikanthan and Karlamangla [12] have demonstrated that muscle mass is a predictor of longevity when taking into account the all-cause mortality in North American adults (aged over 55 or 65 years for men and women, respectively). One of the main ways in which sarcopenia contributes to the disease is that it alters muscular turnover and metabolism [15,16]. Moreover, older adults exhibit a decreased anabolic response to protein feeding [17,18], which is a mechanism underpinning the loss of muscle mass in sarcopenic individuals.…”
Section: Introductionmentioning
confidence: 99%